“Pulling Telescoped Phantoms Out of the Stump”: Manipulating the Perceived Position of Phantom Limbs Using a Full-Body Illusion - Schmalzl, Laura; Thomke, Erik; Ragnö, Christina; Nilseryd, Maria; Stockselius, Anita; Ehrsson, H. H. (Frontiers in Human Neuroscience, 2011)
Most amputees experience phantom limbs, or the sensation that their amputated limb is still attached to the body. Phantom limbs can be perceived in the location previously occupied by the intact limb, or they can gradually retract inside the stump, a phenomenon referred to as “telescoping”. Telescoping is relevant from a clinical point of view, as it tends to be related to increased levels of phantom pain. In the current study we demonstrate how a full-body illusion can be used to temporarily revoke telescoping sensations in upper limb amputees. During this illusion participants view the body of a mannequin from a first person perspective while being subjected to synchronized visuo-tactile stimulation through stroking, which makes them experience the mannequin’s body as their own. In Experiment 1 we used an intact mannequin, and showed that amputees can experience ownership of an intact body as well as referral of touch from both hands of the mannequin. In Experiment 2 and 3 we used an amputated mannequin, and demonstrated that depending on the spatial location of the strokes applied to the mannequin, participants experienced their phantom hand to either remain telescoped, or to actually be located below the stump. The effects were supported by subjective data from questionnaires, as well as verbal reports of the perceived location of the phantom hand in a visual judgment task. These findings are of particular interest, as they show that the temporary revoking of telescoping sensations does not necessarily have to involve the visualization of an intact hand or illusory movement of the phantom (as in the rubber hand illusion or mirror visual feedback therapy), but that it can also be obtained through mere referral of touch from the stump to the spatial location corresponding to that previously occupied by the intact hand. Moreover, our study also provides preliminary evidence for the fact that these manipulations can have an effect on phantom pain sensations.